Prevalencia de Mycobacterium spp. en canales de bovinos faenados en el matadero municipal del cantón Portoviejo - Gómez Párraga, Marlon Vicente (2021)
The purpose of this research was to determine the incidence of the causative agent of Bovine Tuberculosis (Mycobacterium spp.) in the carcasses of cattle slaughtered in the municipal slaughterhouse of Portoviejo canton, this zoonotic disease is very harmful. The presence of TB-compatible lesions in lymph nodes was identified. This work was carried out in the municipal slaughterhouse of the Portoviejo canton, the sampling was carried out between the months of January and April 2020, with a sample of the population of 295 cattle from the Portoviejo canton and neighboring cantons, the study consisted of observing the slaughter of the animals and the subsequent evaluation of the channels and lymph nodes, the second part of this investigation was carried out in the laboratories of INSPI- Dr. Leopoldo Izquieta Pérez in Guayaquil city, where the microbiological diagnosis was carried out by means of the culture (Stonebrick and Ogawa Kudoh) specific for M bovis, according to international recommendations they are the most effective techniques to make the diagnosis, then the Ziehl Neelsen stain was performed, which is a rapid differential technique, of low sensitivity, very favorable to detect TB caused by M. bovis, in which it was determined that there is a prevalence of 1.69% (5/295) of TB considered high prevalence in the region.